2013
DOI: 10.1001/jamainternmed.2013.6036
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the Prognostic Expectations of Seriously Ill Patients Undergoing Hemodialysis and Their Nephrologists

Abstract: IMPORTANCE Patients undergoing hemodialysis have an annual mortality rate exceeding 20%, comparable to many types of cancer. Past research has shown that patients with cancer overestimate their likelihood of survival relative to their physicians, but this relationship has not been examined in patients with noncancer diagnoses. Perceptions of prognosis and transplant candidacy may influence goals of care.OBJECTIVES To compare the perceptions of hemodialysis patients and their nephrologists concerning prognosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
172
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(182 citation statements)
references
References 42 publications
8
172
2
Order By: Relevance
“…A qualitative study found that ESKD patients tended to wait for health professionals to raise ACP rather than raise it themselves 48 , while another found that nephrologists discussed EOL issues based on prognosis but struggled to identify a suitable juncture 103 . Without appropriately sensitive communication about prognosis, patients on dialysis may dramatically over-estimate their life expectancy 104 . A further study found that nurses felt uncomfortable raising ACP for fear of upsetting patients, eliciting anger from families, and being denigrated by senior staff 61 .…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study found that ESKD patients tended to wait for health professionals to raise ACP rather than raise it themselves 48 , while another found that nephrologists discussed EOL issues based on prognosis but struggled to identify a suitable juncture 103 . Without appropriately sensitive communication about prognosis, patients on dialysis may dramatically over-estimate their life expectancy 104 . A further study found that nurses felt uncomfortable raising ACP for fear of upsetting patients, eliciting anger from families, and being denigrated by senior staff 61 .…”
Section: Discussionmentioning
confidence: 99%
“…If the patient is too old or is otherwise at high risk for transplantation, this should be explained to the patient during the informed consent discussion. 3 This principle of informed consent is reflected in the US Centers for Medicare and Medicaid Services requirement for providers to document on Form-2728 within 45 days of dialysis initiation either KT provision of information (KTPI) or a reason for not giving information. 4 During the first 2 years in which KTPI questions were included, only approximately 70% of incident patients with ESRD were reported by their provider to be informed at the time of Form-2728 filing.…”
mentioning
confidence: 99%
“…Frailty is extremely common among patients receiving hemodialysis in the United States (35) and is associated with early dialysis start and high mortality rates (36). For patients who are most frail or have multiple comorbidities, determining frailty via available tools, such as the FRAIL (Fatigue, Resistance, Ambulation, Illnesses, and Loss of Weight) (37) or Rockwood (38) index, can help address the optimism bias often encountered in patients and families with critical illness; in turn, unrealistic expectations regarding treatment benefits can be avoided (39,40). Best case/worst case scenarios can be helpful for patients and families to more accurately appreciate a full spectrum of possible outcomes.…”
Section: Preserving Patient Autonomymentioning
confidence: 99%
“…Second, physicians often bring their biases to the bedside, which can affect the patients' perception and ultimate decision (51,69). Finally, patients and family members of seriously ill patients tend to have a significant optimism bias when faced with dire prognosis, which may affect their choices as surrogate decision-makers for their loved one (39,40). Shared decision-making that allows a patient's goals to be met as accurately as possible should still be the goal.…”
Section: Shared Decision-making As An Answer To the Ethical Challengesmentioning
confidence: 99%